2011
DOI: 10.1007/s11999-011-1921-z
|View full text |Cite
|
Sign up to set email alerts
|

Women Recover Faster Than Men after Standard Knee Arthroplasty

Abstract: Background Specific anatomic differences are believed to account for gender-specific function and health-related quality of life after TKA. However, there are conflicting data in the literature regarding these gender-specific outcomes, especially as woman appear to have surgery later in the course of the disease compared with men. Questions/purposes We asked whether (1) women had worse knee function and health-related quality of life after TKA compared with men, (2) lower improvements in scores, and (3) slower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
31
3
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 16 publications
5
31
3
1
Order By: Relevance
“…There is conflicting evidence if women recover faster than men after TKA [34]. We could not find any significant effect of gender, age and BMI on PROM values and satisfaction ratings for both THA and TKA patients.…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…There is conflicting evidence if women recover faster than men after TKA [34]. We could not find any significant effect of gender, age and BMI on PROM values and satisfaction ratings for both THA and TKA patients.…”
Section: Discussioncontrasting
confidence: 78%
“…THA patients showed the greatest improvements within the first 3 months, while TKA patients continuously improved over time. A similar observation was made by Liebs and coworkers who showed continuous improvements in WOMAC and SF-36 values over 24 months after TKA [34]. Likewise, Papakostidou et al [35] pointed out that large functional improvements will be achieved between 6 weeks and 3 months after TKA, but further improvements were seen up to 1 year postoperatively.…”
Section: Discussionsupporting
confidence: 66%
“…The literature we evaluated seems to largely support our findings in this study (Table 2). However, not all studies, which analyzed gender showed a difference in functional outcomes following TKA [21].…”
Section: Discussionmentioning
confidence: 95%
“…However, an absence of clinically significant sex differences for WOMAC ® pain and function from one year following surgery has been demonstrated. 26,28 Kennedy et al suggest similarities exist in rates of recovery following TKR between men and women 29 although faster recovery in women in the first six months following TKR (measured by WOMAC ® pain and function) has been reported more recently 30 …”
Section: Discussionmentioning
confidence: 99%